Clinical efficacy of the optimal biological dose in early-phase trials of anti-cancer targeted therapies. (October 2019) - Corbaux, Pauline; El-Madani, Mévidette; Tod, Michel; Péron, Julien; Maillet, Denis; Lopez, Jonathan; Freyer, Gilles; You, Benoit
Abstract: Background: Determining the optimal biological dose (OBD) has been described as an alternative strategy to the maximum tolerated doses (MTDs) for identifying the recommended phase II trial doses (RP2Ds) of phase I anti-cancer therapies. However, the clinical relevance is still unknown. An extensive review was performed to assess if the OBDs defined in early-phase trials were useful for subsequent drug development and approvals. Methods: All the molecular targeted therapies approved by the Food and Drug Administration (FDA) in solid oncology or in haematological malignancies before July 2018 were listed through the National Cancer Institute Database. The early-phase trial publications investigating these drugs as single agents were retrieved and analysed to identify the drugs for which OBDs were reported. The publications of subsequent pivotal efficacy clinical trials leading to the approvals were retrieved, and OBDs compared with the final labelled doses and dosing schedules. Results: A total of 87 early-phase trial publications were analysed, corresponding to 81 FDA-approved targeted therapies. OBDs were reported for 40% (32/81) of these drugs (19 small molecules, 13 monoclonal antibodies). MTDs were not identified for 59% (19/32) of molecules. When the OBDs were selected as the RP2Ds (18/32 molecules), the final FDA-approved doses were consistent with the OBDs for 83% of the drugs, which is much higher than the previously reported 58% rate when MTDs were chosen as the RP2Ds. Conclusion: Although still poorly investigated, the OBD may be a relevant and complementary end-point for early-phase trials of targeted therapies. Highlights: Optimal biological dose (OBD) is the lowest dose associated with biological efficacy in early-phase trials. OBDs were insufficiently reported in early-phase trials of targeted therapies. When selected as recommended phase II trial doses, OBDs were frequently consistent with Food and Drug Administration–approved doses. OBD may be a relevant end-point for drug development of novel targeted therapies.